2021
DOI: 10.1111/jav.02782
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally induced flight costs do not lead to increased reliance on supplemental food in winter by a small songbird

Abstract: Each year hundreds of millions of people intentionally feed wild animals throughout the world. For decades, concerns have persisted regarding the potential for intentional feeding to promote dependency on human-supplemented food, particularly during energetically demanding periods of the annual cycle. In this study, we evaluated whether individuals subjected to experimentally increased flight costs responded by increasing their use of supplemental feeders in a wild, free-ranging population of the black-capped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…It's been shown that bird feeders and other methods of supplying concentrated food opportunities for animals can sometimes increase the spread of pathogens, and in some (but not all) cases there's evidence that increasing food options changes animals' behaviors in other ways as well. (Becker et al, 2015;Plummer et al, 2015;Plummer et al, 2019;Senigaglia et al, 2019;Lajoie et al, 2021) Such ecological concerns are of the sort that require a far broader investigation into human activities that impact animals' environments, from other sports-related concerns such as around land use for golf courses to basic questions of creating and designing cities for human habitation.…”
Section: Using Non-human Animals In Sportmentioning
confidence: 99%
“…It's been shown that bird feeders and other methods of supplying concentrated food opportunities for animals can sometimes increase the spread of pathogens, and in some (but not all) cases there's evidence that increasing food options changes animals' behaviors in other ways as well. (Becker et al, 2015;Plummer et al, 2015;Plummer et al, 2019;Senigaglia et al, 2019;Lajoie et al, 2021) Such ecological concerns are of the sort that require a far broader investigation into human activities that impact animals' environments, from other sports-related concerns such as around land use for golf courses to basic questions of creating and designing cities for human habitation.…”
Section: Using Non-human Animals In Sportmentioning
confidence: 99%
“…Wildlife managers have also utilized supplemental feeding to support the conservation of endangered species, replacing diminished resources and providing foods free of environmental contaminants [24]. Despite a growing body of literature on the subject, the debate regarding the benefits versus the adverse effects of supplemental feeding to wild birds is a complex question and has yet to be resolved [27,[40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%